Serum neurofilament light chain in distinct phenotypes of amyotrophic lateral sclerosis: a longitudinal, multicenter study - Meyer, Thomas; Dreger, Marie; Grehl, Torsten; Weyen, Ute; Kettemann, Dagmar; Weydt, Patrick; Günther, René; Lingor, Paul; Petri, Susanne; Koch, Jan Christoph; Großkreutz, Julian; Rödiger, Annekathrin; et al. (European journal of neurology, 2024)
Objective To assess the performance of serum neurofilament light chain (sNfL) in clinical phenotypes of amyotrophic lateral sclerosis (ALS). Methods In 2949 ALS patients at 16 ALS centers in Germany and Austria, clinical characteristics and sNfL were assessed. Phenotypes were differentiated for two anatomical determinants: (1) upper and/or lower motor involvement (typical, typMN; upper/lower motor neuron predominant, UMNp/LMNp; primary lateral sclerosis, PLS) and (2) region of onset and propagation of motor neuron dysfunction (bulbar, limb, flail-arm, flail-leg, thoracic onset). Phenotypes were correlated to sNfL, progression, and survival. Results Mean sNfL was - compared to typMN (75.7 pg/mL, n = 1791) - significantly lower in LMNp (45.1 pg/mL, n = 413), UMNp (58.7 pg/mL n = 206), and PLS (37.6 pg/mL, n = 84). Also, sNfL significantly differed in the bulbar (92.7 pg/mL, n = 669), limb (64.1 pg/mL, n = 1305), flail-arm (46.4 pg/mL, n = 283), flail-leg (53.6 pg/mL, n = 141), and thoracic (74.5 pg/mL, n = 96) phenotypes. Binary logistic regression analysis showed highest contribution to sNfL elevation for faster progression (odds ratio [OR] 3.24) and for the bulbar onset phenotype (OR 1.94). In contrast, PLS (OR 0.20), LMNp (OR 0.45), and thoracic onset (OR 0.43) showed reduced contributions to sNfL. Longitudinal sNfL (median 12 months, n = 2862) showed minor monthly changes (<0.2%) across all phenotypes. Correlation of sNfL with survival was confirmed (p < 0.001). Conclusions This study underscored the correlation of ALS phenotypes - differentiated for motor neuron involvement and region of onset/propagation - with sNfL, progression, and survival. These phenotypes demonstrated a significant effect on sNfL and should be recognized as independent confounders of sNfL analyses in ALS trials and clinical practice.
Online veröffentlicht: 10. Juni 2024
Gesehen am 28.10.2024